2019
DOI: 10.1002/ppul.24247
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of acute asthma therapy response in children with moderate‐to‐severe asthma exacerbations

Abstract: Background: We documented inter-individual variability in the response to acute asthma therapy in children, attributed in part to five clinical factors (oxygen saturation, asthma severity score, virus detection, fever, symptoms between exacerbations; DOORWAY study). The contribution of genetic determinants of failure of acute asthma management have not been elucidated.Objective: We aim to determine single nucleotide polymorphisms (SNP) associated with emergency department (ED) management failure in children.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…AEs focused on polymorphisms in genes previously implicated in asthma or in viral pathways [1], such as the Interleukin 33 (IL33) [50], vitamin D receptor (VDR) [54], or SERPINE1 gene encoding for the plasminogen activator inhibitor-1 (PAI-1) [52] (Table 1). For instance, adding several asthma-related variants at SPATS2L and IL33 that were associated with ED management failure to ED-related clinical scores improved the predictive capability for ED management failure compared with the clinical model alone (area under the curve [AUC]: 0.82 vs. 0.79, p = 0.0004) [50]. Moreover, an expression quantitative trait loci (eQTL) analysis of respiratory syncytial virus (RSV)related genes narrowed down the modulatory effect of RSV infection on a CEACAM3 locus for AEs [53].…”
Section: Candidate-gene Association Studies Most Candidate-gene Assoc...mentioning
confidence: 99%
“…AEs focused on polymorphisms in genes previously implicated in asthma or in viral pathways [1], such as the Interleukin 33 (IL33) [50], vitamin D receptor (VDR) [54], or SERPINE1 gene encoding for the plasminogen activator inhibitor-1 (PAI-1) [52] (Table 1). For instance, adding several asthma-related variants at SPATS2L and IL33 that were associated with ED management failure to ED-related clinical scores improved the predictive capability for ED management failure compared with the clinical model alone (area under the curve [AUC]: 0.82 vs. 0.79, p = 0.0004) [50]. Moreover, an expression quantitative trait loci (eQTL) analysis of respiratory syncytial virus (RSV)related genes narrowed down the modulatory effect of RSV infection on a CEACAM3 locus for AEs [53].…”
Section: Candidate-gene Association Studies Most Candidate-gene Assoc...mentioning
confidence: 99%
“…For instance, rs928413 is a SNP significantly associated with increased risk of asthma when carrying the AA genotype, while individuals with the heterozygous genotype (GA) have a decreased risk of asthma compared to those who do not carry the mutated allele [ 233 ]. While most association studies of SNPs focus on the risk and susceptibility of asthma, Tse et al demonstrated that SNPs rs1342326 and rs7037276 are inversely associated with emergency department failure in children with moderate to severe asthma [ 232 ], suggesting those that carry these SNPs may have a better response to common asthma therapy. Findings of genome-wide association studies show that ethnic background can have an essential role in determining the direction of association between different SNPs and disease risk or susceptibility [ 240 ].…”
Section: Variants Of Alarmins Genes In Asthmamentioning
confidence: 99%
“…We next examined 47 previous genetic loci for asthma exacerb ations 7,8,12,13,[34][35][36] and moderate-to-severe asthma 37 for association with asthma exacerbations in the discovery phase. A total of 5 variants had p < .05 in Europeans, 2 in Hispanics/Latinos, 5 in African Americans, and 1 in Singaporean Chinese (Table S16).…”
Section: Validationofpreviousassociationsmentioning
confidence: 99%